2018
DOI: 10.1055/s-0038-1660812
|View full text |Cite
|
Sign up to set email alerts
|

Functional Effects of the Adams Procedure: A Retrospective Intervention Study

Abstract: Injury to the distal radioulnar joint (DRUJ) causes swelling and ulnar-sided wrist pain. The Adams procedure stabilizes the DRUJ and shows promising short-term results. We studied the long-term functional outcome in patients who underwent the Adams procedure. We also tested the null hypothesis that there would be no difference in range of motion (ROM) and grip strength between the operated wrist compared to the unaffected side. We identified 74 consecutive patients that were operated from March 2005 to Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
0
14
0
4
Order By: Relevance
“…En los trabajos anteriores, [16][17][18] se describían diferentes tipos de reconstrucción quirúrgica abierta del CFCT. En los últimos años, se han publicado series de casos de cirugía abierta, 19,20 y también series de reconstrucción con cirugía abierta asistida por artroscopia. 21,22 Las técnicas quirúrgicas se esquematizan en la ►Fig.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…En los trabajos anteriores, [16][17][18] se describían diferentes tipos de reconstrucción quirúrgica abierta del CFCT. En los últimos años, se han publicado series de casos de cirugía abierta, 19,20 y también series de reconstrucción con cirugía abierta asistida por artroscopia. 21,22 Las técnicas quirúrgicas se esquematizan en la ►Fig.…”
Section: Resultsunclassified
“…2B), y publicó los resultados junto con Berger en 2002. 17 Posteriormente, cuatro equipos de cirujanos realizaron el procedimiento de Adams en sus series, [18][19][20]24 y la mayoría de las técnicas diseñadas posteriormente recogidas en esta revisión sistemática son modificaciones de este procedimiento, 21,22,25,26 que actualmente es el tratamiento patrón oro para la inestabilidad crónica de la ARCD.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…At a mean 1.6 years after surgery, 15 had excellent or good results, while one with a poor outcome owing to residual subluxation improved with a secondary procedure. Kootstra et al. (2018) found that three of 23 Adams–Berger procedures failed at a mean 5 years after the primary operation.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, surgical repairs of foveal TFCC tears have been performed using a dorsal approach with acceptable clinical outcomes, 7,12,[16][17][18] but the literature has suggested the potential for better functional outcomes via a volar approach as was previously described by Moritomo. 12,[19][20][21] During a dorsal approach to the TFCC, the foveal lesion is challenging to visualize because of the ECU tendon subsheath.…”
mentioning
confidence: 99%